2009
DOI: 10.1007/s10646-009-0428-9
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of the fungicide azoxystrobin in outdoor brackish water microcosms

Abstract: The effects of the strobilurin fungicide azoxystrobin were studied in brackish water microcosms, with natural plankton communities and sediment. Two experiments were conducted: Experiment 1 (nominal conc. 0, 15 and 60 µg/L, 24-L outdoor microcosms for 21 days) and a second, follow-up, Experiment 2 (nominal conc. 0, 3, 7.5, 15 μg/L, 4-L indoor microcosms for 12 days). The microcosms represent a simplified brackish water community found in shallow semi-enclosed coastal areas in agricultural districts in the Balt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
37
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 21 publications
(15 reference statements)
7
37
1
Order By: Relevance
“…Pesticides and other organic pollutants not only affect phytoplankton biomass but also exert persistent effects on phytoplankton species composition and structure due to differing tolerances between phytoplankton taxa (Seguin et al 2002;Wendt-Rasch et al 2003;Gustafsson et al 2010;Katia et al 2010). Results from our previous study showed that cypermethrin exerted significant effects on the growth and physiological parameters of phytoplankton at recommended exposure levels for treating farmed fish and in natural sea waters using single-species tests, and different sensitivities among phytoplankton taxa might result in shift in phytoplankton community structure (Wang et al 2010a(Wang et al , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Pesticides and other organic pollutants not only affect phytoplankton biomass but also exert persistent effects on phytoplankton species composition and structure due to differing tolerances between phytoplankton taxa (Seguin et al 2002;Wendt-Rasch et al 2003;Gustafsson et al 2010;Katia et al 2010). Results from our previous study showed that cypermethrin exerted significant effects on the growth and physiological parameters of phytoplankton at recommended exposure levels for treating farmed fish and in natural sea waters using single-species tests, and different sensitivities among phytoplankton taxa might result in shift in phytoplankton community structure (Wang et al 2010a(Wang et al , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…At 20°C, the solubility of AZX in water is 6.7 mg/L (pH 5.2 and 7.0) and it has a low vapor pressure of 1.1 9 10 -7 mPa (Rodrigues et al 2013). AZX dissition rates from water with half-life values of 18 days and 15-25 days were also determined by Zafar et al (2012); Gustafsson et al (2010), respectively. Analytical measurements of AZX were not carried out in the aqueous media of exposure used but the design of the present study was made taking into account the physicochemical characteristics of AZX detailed above.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, its impact on non-target species is not fully known (Deb et al 2010) and its use has created concern because the mode of action is not specific to just fungi. AZX concentrations in run-off waters range from 1 to 30 lg/L (Berenzen et al 2005;Deb et al 2010;Battaglin et al 2011), levels considered toxic to calanoid copepods (Gustafsson et al 2010) and fish like the Atlantic salmon (Olsvik et al 2010). In relation to genotoxicity, AZX showed to be clastogenic in invertebrates (Han et al 2014) as well as in vertebrates (Bony et al 2008).…”
mentioning
confidence: 99%
“…However, it is difficult to draw any firm conclusions on environmental effects based solely on laboratory data (Hall et al 1999), why it is common practice by regulatory agencies to apply safety factors in risk assessment to compensate for uncertainties regarding how well laboratory data represent the environmental situation. It is even more difficult to draw any conclusions regarding synergistic effects or effects in brackish water ecosystems (Gustafsson et al 2010).…”
Section: Resultsmentioning
confidence: 99%